Accuracy of gradient diffusion method for susceptibility testing of dalbavancin and comparators. Issue 3 (4th March 2022) - Leroy, A. G.; Lavigne-Quilichini, V.; Le Turnier, P.; Loufti, B.; Le Breton, E.; Piau, C.; Kempf, M.; Pantel, A.; Amara, M.; Neuwirth, C.; Sanchez, R.; Guinard, J.; et al.
ABSTRACT: Objectives: This multicenter study aimed to assess the performances of gradient diffusion (GD) method in comparison to broth microdilution (BMD) method for susceptibility testing of dalbavancin, daptomycin, vancomycin, and teicoplanin. Methods: Minimum Inhibitory Concentrations (MICs) were retrospectively determined concomitantly by BMD and GD methods, for 93 staphylococci and enterococci isolated from clinical samples. BMD was considered as the gold standard. Essential (EA) and categorical agreements (CA) were calculated. Discordant categorical results were categorized as major (ME) and very major errors (VME). Results: EA and CA were 95.7% and 96.8%, 82.8% and 100%, 97.8% and 96.8%, and 94.6% and 95.7% for dalbavancin, daptomycin, vancomycin, and teicoplanin respectively. Concerning dalbavancin, 3 ME without any VME were observed and discrepancies were low (≤ to 2 two-fold dilutions) between both methods. VME were noted in 1 and 3 cases for vancomycin and teicoplanin, respectively, and resulted from 1 two-fold dilution discrepancy in each case. EA was lower for daptomycin. When they were discrepant, BMD MICs were systematically higher than GD ones. Nevertheless, no categorical discrepancy was noted. Conclusions: GD appears as an acceptable and convenient alternative for dalbavancin, vancomycin, and teicoplanin MICs determination. Our study also emphasizes how achieving accurate daptomycin MICs remains challenging.